Business Intelligence (BI) Approach for Traffic Accidents Analysis - Madnira, Shujana (International Journal of Information Technology and Computer Science Applications, 2023)
‘FLCRASH’ is the data source used for this report that consists of crash data from the year 2008 to 2009. The purpose of this report is to find ways to reduce the number of fatal accidents on the road by identifying the main culprits on why these accidents happen so frequently. Business intelligence is used in the process of finding the relationships and trends in the major causes of the crashes. The technologies related to Business Intelligence that will help in aiding the organization to their goal are also discussed along with the supporting factors for the use of Business Intelligence for the organization. A dashboard has been created from various graphs and charts for easy viewing and understanding of the situation so logical decisions can be made based on it. This report seeks to help us better understand the nature of why traffic accidents happen in the first place and how to prevent them from happening in the future.